BIOETANOL GEMBILI LIAR (Dioscorea Esculenta L)SEBAGAI OCTANE IMPROVER BAHAN BAKAR BENSIN RAMAH LINGKUNGAN - Heru Mulyantoro, Eko Marwanto, Andra Ari P., Dwi Hermayantiningsih (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research is intended to 1) to know the production process of bioetanol fromwild purplish edible tuber, 2) to know the influence of purplish edible tuber bioetanoltoward the octane rate of gasoline, 3) to know the influence of wild-purplish edible tuberbioetanol as octane improver of gasoline toward the emission of motorcycle combustion.This research employed experiment method involving the preliminary research ofwild- purplish edible tuber bioetanol, the production of wild-purplish edible tuber bioetanol,blended bioetanol and gasoline, eco-friendly gasoline research, and analysis.The result of the research reveals that 1) the production process of wild-purplishedible tuber is initiated by the hydrolysis process, fermentation, and distillation. Theoptimum period to get etanol of the purplish edible tuber with the treatment 1.2 gramof yeast for 100gram of purplish edible tuber is 46 hours of fermentation. The employeddestillation is highrise distillation to get etanol content 96%, 2) the influence of thebioetanol mixture in gasoline can increase octane rate at sequentially mixture 10%,20%, 30% respectively 3 point, 2.3 point, and 4.8 point, 3) the influence of bioetanolmixture in gasoline toward the emission of exhaust gas, carbon monoxide (CO) at allmixture ratio decreases while the emission of hydrocarbon decreases at the mixtureratio 10% and increases on the 20% and 30%.Key Words: bioetanol, wild purplish edible tuber, gasoline